L’assurance-vie dans une période de transformation - Ross, Jacques A. (Assurances, 1984)
The author looks at the current problems of life insurance: low rates, cancellation of many policies due to inflation and the high rates of interest. lnsureds are also becoming more confident of their ability to arrange their investments themselves. How can the industry adapt to this new situation, and at the same time keep its traditional reliability? The author suggests some answers, and compares the success of previous years with the new approach which is now necessary.